The Impact of Colonial Thinking Legacy on the Production of Knowledge about the Fine Arts in Southeast Asia - Simanullang, Pernandus (Indonesian Journal of History Education, 2023)
The experience of art history in Southeast Asia is an unforgettable part of society. Through art before and after thought or art has existed. The arrival of foreigners to Southeast Asia enriched new philosophies for every place that had been influenced by colonial thought. Through the new philosophy, from a perspective, thinking, and doing something, especially in art, has undergone a significant change. This change is a fundamental part but the tradition is still maintained. The impact of change through the influence of colonial thought produces new knowledge in maintaining and preserving the arts, culture, and customs that exist in every country in Southeast Asia. It can be seen that to this day it is the main place for tourists who come to Southeast Asia. Postcolonialism questions and rediscovers modes of cultural perception, and ways of seeing and being seen. In anthropology, postcolonialism studies human relations in colonial countries and subaltern societies exploited by colonial rule. Postcolonialism describes, explains, and illustrates the ideology of neocolonialism by taking the humanities, history, and political science, philosophy and sociology, anthropology, and. So post-colonialism adds or brings a new identity to each country in Southeast Asia but still maintains and preserves traditional arts and culture.